Dysphagia as an Uncommon Presentation of Disseminated Tuberculosis: A Case Report - Shil, Bimal Chandra; Banik, Ranjit Kumar; Saha, Shasanka Kumar; Uddin, Md Royes; Saifullah, ANM; Rashid, Md Mamun ur; Mahbub, Imteaz (Journal of Bangladesh College of Physicians and Surgeons, 2020)
This is a case report of a 57-year old farmer who presented with a 4 months history of dysphagia and weight loss. Upper gastrointestinal endoscopy revealed submucosal swellings with overlying ulcers at mid to lower part of esophagus. Repeated histopathological evaluation of endoscopic esophageal tissue biopsies showed nonspecific findings. Endoscopic ultrasound showed a hypoechoic mass at submucosal layer with periesophageal lymphadenopathy. Endosonogram guided FNA materials depicted caseating granulomas. Patient was managed with anti-tuberculosis therapy. Follow up endosonography after therapy revealed resolution of the growth and the mediastinal lymph node enlargement and patient was symptomatically improved. J Bangladesh Coll Phys Surg 2020; 38(3): 150-154